Perancangan Desain Karakter Dalam Game Entangled Untuk Usia 19-25 Tahun - Diah Permatasari; Aninditya Daniar; Alfian Candra Ayuswantana (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
The Entangled game is designed as an interactive medium to convey the problem of ghost nets to the 19–25 age group through a visual novel format that relies on narrative and visuals as a means of communication. This medium is presented to highlight the problem of ghost nets which are a serious threat to marine ecosystems because they destroy habitats, endanger marine biota, and impact the social and economic aspects of coastal communities, but are still poorly understood by the younger generation due to the limited availability of engaging and communicative educational media. In designing this game, character design plays a key supporting element that helps convey conservation messages emotionally and narratively through character representation, dialogue, and relationships between characters in the storyline. The method used is a mixed method with data collection through interviews, literature studies, and questionnaires, which are then developed using the Game Development Life Cycle (GDLC) approach to ensure the game design process runs systematically.